LEARNING DIFFICULTIES: REFLECTIONS ABOUT DYSCALCULIA - Maria Batista de Lima, Ana; Naiara Vicente de Góes, Ana; Nestor Felipe Gaudencio, Robson (Revista Gênero e Interdisciplinaridade, 2023)
Given the various difficulties found in the universe of mathematics, it is relevant to seek to understand what are the common problems in relation to skills with numbers. Among such problems, dyscalculia stands out, a subject that began to be a source of research in 1924, but which is still little discussed. Thus, this study aims to bring reflections on this theme, through a theoretical discussion, addressing the historical path, characteristics, as well as how dyscalculia can affect the student. In this sense, it is intended to present strategies for a better performance of the discalculic student, with a view to an effective learning with regard to the development of calculations.